Local anatomy, stimulation site, and time alter directional deep brain stimulation impedances - Olson, Joseph W.; Gonzalez, Christopher L.; Brinkerhoff, Sarah; Boolos, Maria; Wade, Melissa H.; Hurt, Christopher P.; Nakhmani, Arie; Guthrie, Bart L.; Walker, Harrison C. (Frontiers in Human Neuroscience, 2022)
Directional deep brain stimulation contacts provide greater spatial flexibility for therapy than traditional ring-shaped electrodes, but little is known about longitudinal changes of impedance and orientation. We measured monopolar and bipolar impedance of DBS contacts in 31 patients who underwent unilateral subthalamic nucleus deep brain stimulation as part of a randomized study (SUNDIAL, NCT03353688). At different follow-up visits, patients were assigned new stimulation configurations and impedance was measured. Additionally, we measured the orientation of the directional lead during surgery, immediately after surgery, and one year later. Here we contrast impedances in directional versus circular contacts with respect to local anatomy, active stimulation contact(s), and over time. Directional contacts display larger impedances than circular contacts. Impedances generally increase slightly over the first year of therapy, save for a transient decrease immediately post-surgery under general anesthesia during pulse generator placement. Local impedances decrease at active stimulation sites, and contacts in closest proximity to internal capsule display higher impedances than other anatomic sites. DBS leads rotate slightly in the immediate postoperative period (typically less than the angle of a single contact) but otherwise remain stable over the following year. These data provide useful information for setting clinical stimulation parameters over time.